2010
DOI: 10.1007/s00421-010-1684-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lemon verbena supplementation on muscular damage markers, proinflammatory cytokines release and neutrophils’ oxidative stress in chronic exercise

Abstract: Intense exercise is directly related to muscular damage and oxidative stress due to excessive reactive oxygen species (ROS) in both, plasma and white blood cells. Nevertheless, exercise-derived ROS are essential to regulate cellular adaptation to exercise. Studies on antioxidant supplements have provided controversial results. The purpose of this study was to determine the effect of moderate antioxidant supplementation (lemon verbena extract) in healthy male volunteers that followed a 90-min running eccentric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 55 publications
0
38
0
3
Order By: Relevance
“…While moderate exercise may enhance both immune function and antioxidant system over sedentary levels, prolonged and high-intensity exercise overcome the antioxidant systems and may impair immune function. This negative response is more apparent as the intensity and duration of exercise increase (Gleeson 2007;Funes et al 2011).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…While moderate exercise may enhance both immune function and antioxidant system over sedentary levels, prolonged and high-intensity exercise overcome the antioxidant systems and may impair immune function. This negative response is more apparent as the intensity and duration of exercise increase (Gleeson 2007;Funes et al 2011).…”
Section: Introductionmentioning
confidence: 89%
“…However, associated with this important increase in free radical production during strenuous exercise, there is an over-expression of inXammatory cytokines which have also been shown to contribute to the above commented aspects related to highintensity exercise (Gleeson 2007;Funes et al 2011).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, several studies have indicated that antioxidant supplementation induces a positive effect (1, 2), a negative effect (3,4), or no effect (5, 6) on muscle performance. Likewise, several studies have reported that antioxidant supplementation attenuates oxidative stress (7)(8)(9), others have reported that it induces a prooxidant effect (10)(11)(12)(13), and others have reported that it does not affect redox status (5,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed a not univocal strategy in the timing of supplementation (pre exercise, during exercise, post exercise) has been adopted demonstrating de facto a lack of a univocal and definite and generally accepted mechanism underlying the correlation between exercise, muscle damage, and antioxidant activity. As a matter of facts several studies have examined the effects of antioxidants on indices of ROS-induced muscle damage in exercise and suggested that antioxidant supplementation may exert some protection particularly in relation to bouts of resistance exercise in untrained or physically active individuals [30][31][32][33][34][35] as demonstrated by a reduced inflammation [35][36][37][38][39], force loss [30, 40,41], and fatigue appearance [42,43] and no evidence for any beneficial effect on performance [44] [54][55][56][57]. The lack of effects appears to be particularly evident in highly trained individuals whose adaptation to increased exposure to oxidation is normally able to promote a secondary increase of the endogenous antioxidant defenses that reduce the risk of oxidative damage [58,59] Therefore even following extreme exercise paradigms, unlike short periods of modest exercise [60], indications of oxidative damage may lack in well trained athletes [61].…”
Section: Antioxidant/vitaminesmentioning
confidence: 99%